A Change of Scenery: Does Exposure to Images of Nature Affect Delay Discounting and Food Desirability? - Clarke, Katie; Higgs, Suzanne; Holley, Clare E.; Jones, Andrew; Marty, Lucile; Hardman, Charlotte A. (Frontiers in Psychology, 2021)
Previous research suggests that exposure to nature may reduce delay discounting (the tendency to discount larger future gains in favour of smaller immediate rewards) and thereby facilitate healthier dietary intake. This pre-registered study examined the impact of online exposure to images of natural scenes on delay discounting and food preferences. It was predicted that exposure to images of natural scenes (vs. images of urban scenes) would be associated with (i) lower delay discounting; (ii) higher desirability for fruits and vegetables (and lower desirability for more energy-dense foods); and (iii) delay discounting would mediate the effect of nature-image exposure on food desirability. Adult participants (N = 109) were recruited to an online between-subjects experiment in which they viewed a timed sequence of six images either showing natural landscape scenes or urban scenes. They then completed measures of mood, delay discounting (using a 5-trial hypothetical monetary discounting task) and rated their momentary desire to eat four fruits and vegetables (F&V), and four energy-dense foods. There was no statistically significant effect of experimental condition (natural vs. urban image exposure) on delay discounting or food desirability. Bayes factors supported the null hypothesis for discounting (BF01 = 4.89), and energy-dense food desirability (BF01 = 7.21), but provided no strong evidence for either hypothesis for F&V desirability (BF01 = 0.78). These findings indicate that brief online exposure to images of nature does not affect momentary impulsivity or energy-dense food preference, whereas for preference for less-energy dense foods, the evidence was inconclusive.